Coyotes: Friends or Foe of Northern Bobwhite in Southern Texas - Scott E. Henke (National Quail Symposium Proceedings, 2017)
Food habits of 407 coyotes (Canis latrans), intermittently collected in southern Texas from March 1994 to January 1997, were determined from coyote stomachs. Mammalian prey was the most prevalent diet item as calculated by frequency of occurrence and aggregate percent methods, followed by insects, vegetation, birds, and reptiles. The remains of northern bobwhite (Colinus virginianus) or their eggs were found in only 12 coyote stomachs, which constituted 1% of the coyote diet as calculated by the aggregate percent method. Northern bobwhite appear to be an incidental prey item for coyotes in southern Texas. Therefore, coyote removal programs designed to lessen quail depredation appear unwarranted.
Keywords: Canis latrans; Colinus virginianus; coyote; depredation; food habits; northern bobwhite; Texas